Acute Microvascular Changes after Subarachnoid Hemorrhage and Transient Global Cerebral Ischemia. (25th March 2013) - Tso, Michael K.; Macdonald, R. Loch
Abstract : Subarachnoid hemorrhage and transient global cerebral ischemia result in similar pathophysiological changes in the cerebral microcirculation. These changes include microvascular constriction, increased leukocyte-endothelial interactions, blood brain barrier disruption, and microthrombus formation. This paper will look at various animal and preclinical studies that investigate these various microvascular changes, perhaps providing insight in how these microvessels can be a therapeutic target in both subarachnoid hemorrhage and transient global cerebral ischemia.